Consequences of Volcanic Ash Deposition on the Locomotor Performance of the Phymaturus spectabilis Lizard from Patagonia, Argentina - Cabezas, Facundo (2013)
The locomotor performance of lizards depends on their morphological and physiological adaptations to the habitat. However, when the habitat changes dramatically, for example by a volcanic eruption, the performance of lizards may be affected. We registered the vegetation cover, the surface covered by ash, the presence of crevices suitable for Phymaturus and the rocks slopes to analyze the effects of ash accumulation produced by the eruption of Puyehue-Cordon Caulle volcanic complex on microhabitat use and availability of the Phymaturus spectabilis lizard. In addition, we studied the effect of ashes and slope on the locomotor performance of P. spectabilis by registering the maximum speed in sprint runs and long runs under four different treatments (cork and on the level, ashes and on the level, cork and slope, and ashes and slope). Phymaturus spectabilis selected microhabitats unvegetated, with crevices and steep slopes. Regarding locomotor performance, the speed of lizards was negatively affected by the presence of ash only in sprint runs on the level and in long runs with slope. The slope had a negative impact on the speed in all the treatments. These results show that the presence of volcanic ashes in the substrate might have affected the locomotor performance of the lizards, especially in long runs, and hence, the interaction of individuals with the environment, i.e. escaping from predators and social behaviour.